Translational research needs us to go back to basics and collaborate: interview with Lars Sundstrom. (21st July 2016) - Sundstrom, Lars
Lars Sundstrom is Director of Enterprise and Translation at the West of England Academic Health Sciences Network [1 ] (UK), a Professor of Practice in Translational Medicine and Co-Director of the Elizabeth Blackwell Institute for Health Research at Bristol University [2 ] (UK), and an honorary Professor of Medicine at Cardiff University (UK). He has extensive experience in translational medicine and clinical neurosciences, holding positions at several eminent universities. He has also held executive and board-level positions at several SMEs, developing new therapeutics for neurological conditions and tools for drug discovery. He has also been an advisor to several UK and local government task forces and to the European Commission and the European Federation of Pharmaceutical Industry Associations. He was a founding member of the European Brain Council in Brussels, and set up the Severnside Alliance for Translational Research, developing a regional network partnership to link clinical and basic scientists. He was also involved in the creation of Health Research Wales.